Contains NaNbO3 and Na 0.9 K 0.1 NbO3 ferroelectric glass ceramic photocatalytic material and preparation method thereof

The preparation of ferroelectric glass ceramic photocatalytic materials containing NaNbO3 and Na0.9K0.1NbO3 by melting method solves the complex structure and manufacturing process problems of traditional ferroelectric photocatalytic materials, and realizes the efficient photocatalytic performance of the material and the simplified preparation process.

CN116217084BActive Publication Date: 2025-04-29SHAANXI UNIV OF SCI & TECH
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202211676176.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-26
Publication Date
2025-04-29
Estimated Expiration
2042-12-26

AI Technical Summary

Technical Problem

Traditional ferroelectric photocatalytic materials have defects such as non-density structure, complex manufacturing process, difficult to control shape and size, mostly powder, difficult to recover, and opaque, resulting in low photocatalytic efficiency.

Method used

The ferroelectric glass ceramic photocatalytic material containing NaNbO3 and Na0.9K0.1NbO3 was prepared by melting method. By controlling the volume fraction of the crystal phase, the physical properties of the material, such as crystallinity and transparency, are optimized, thereby improving the photocatalytic performance.

Benefits of technology

The simplification of the preparation process and the shortening of the production cycle are achieved, and ferroelectric glass ceramic materials with good transparency characteristics and excellent photocatalytic properties are obtained, which can effectively suppress the recombination of photogenerated electron holes, improve carrier separation efficiency, and broaden the photoresponse range.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116217084B_ABST
    Figure CN116217084B_ABST
Patent Text Reader

Abstract

The present invention discloses a preparation method of a ferroelectric glass-ceramic photocatalytic material containing NaNbO3 and Na 0.9 K 0.1 NbO3, comprising the following steps: 1. Mix 30-35 mol of Na2CO3, 5-10 mol of K2CO3, 35-40 mol of Nb2O5 and 20-30 mol of SiO2 evenly to obtain a mixture; 2. Add the mixture into a crucible preheated to 1150-1250 °C, continue heating to melt the mixture, and keep it warm until there are no bubbles, then pour the melt into a mold preheated to 200 °C to make it shaped; 3. After the melt in step 2 is shaped, quickly transfer it to an annealing furnace, heat it from room temperature to 500-600 °C at a heating rate of 5 °C / min and keep it warm, and then cool it with the furnace to obtain a glass sample; 4. Put the glass sample into a muffle furnace, heat it from room temperature to 700 °C at a heating rate of 5 °C / min and keep it warm, and then cool it with the furnace to obtain a ferroelectric glass-ceramic photocatalytic material containing NaNbO3 and Na 0.9 K 0.1 NbO3, which has excellent photocatalytic performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a ceramic material, specifically a ceramic material containing NaNbO3 and Na 0.9 K 0.1 NbO3 ferroelectric glass ceramic photocatalytic material and preparation method thereof. Background Art

[0002] The use of photocatalytic technology to achieve efficient conversion of solar energy has great potential in alleviating energy crisis and environmental pollution, but its low conversion efficiency hinders its practical application. Inhibiting the recombination of photogenerated electrons and holes, improving the efficiency of carrier separation, and enabling electrons and holes to effectively reach the active sites on the surface of the material to participate in the reaction are the key to significantly improving the photocatalytic degradation performance and promoting the large-scale application of photocatalytic technology.

[0003] In recent years, ferroelectric materials have been widely used in sensors, actuators, nanogenerators, micro-electromechanical devices, memory storage devices, and energy harvesting. The spontaneous polarization in ferroelectric materials is mainly caused by the displacement of the positive and negative charge centers caused by the replacement of some atoms in the crystal, that is, they have a spontaneous dipole moment without applying stress, generating a spontaneous polarization electric field. Due to the existence of spontaneous polarization (Ps), the external electric field can reverse the electric domain and generate residual polarization, thereby generating an internal electric field and a hysteresis loop. This internal electric field forces the photogenerated carriers (e- and h+) holes to move in opposite directions, thereby preventing the recombination of electron-hole pairs and obtaining catalytic activity. Therefore, using the built-in electric field formed by the spontaneous polarization of ferroelectric materials to accelerate the separation and migration of photogenerated electrons and holes has become a hot topic in the field of photocatalytic materials.

[0004] Traditional ferroelectric photocatalytic materials have the following defects: 1. The structure is not dense, and there are a lot of pores and defects inside; 2. The manufacturing process is complicated and the shape and size are difficult to control; 3. Most of them are powders, and the powders need to be loaded onto another carrier and then recycled, which makes recycling difficult and has large recycling losses; 4. They are opaque and cannot transmit light, and can only rely on the surface grains for photocatalytic reactions, with low catalytic efficiency. Compared with ordinary ferroelectric materials, ferroelectric glass-ceramic materials have many excellent properties. It is expected that by controlling the volume fraction of the crystalline phase dispersed in its glass matrix, the physical properties of the material, such as crystallinity and transparency, can be controlled, thereby improving the photocatalytic performance. Summary of the invention

[0005] The object of the present invention is to provide a 0.9 K 0.1 The NbO3 ferroelectric glass ceramic photocatalytic material and the preparation method thereof not only have a simple preparation process but also the prepared glass ceramic has excellent photocatalytic performance.

[0006] In order to achieve the above object, the present invention adopts the following technical solutions:

[0007] A kind of NaNbO3 and Na 0.9 K 0.1 The preparation method of NbO3 ferroelectric glass ceramic photocatalytic material comprises the following steps:

[0008] Step 1, 30-35 mol Na2CO3, 5-10 mol K2CO3, 35-40 mol Nb2O5 and 20-30 mol SiO2 are uniformly mixed to obtain a mixture;

[0009] Step 2, add the mixture into a crucible preheated to 1150-1250°C, continue heating to melt the mixture, and keep warm until there are no bubbles, pour the melt into a mold preheated to 200°C to form it;

[0010] Step 3, after the melt of step 2 is formed, it is quickly transferred to an annealing furnace, heated from room temperature to 500-600°C at a heating rate of 5°C / min and kept warm, and then cooled in the furnace to obtain a glass sample;

[0011] Step 4: Place the glass sample in a muffle furnace, heat it from room temperature to 700°C at a heating rate of 5°C / min and keep it warm. After cooling in the furnace, a glass sample containing NaNbO3 and Na 0.9 K 0.1 NbO3 ferroelectric glass-ceramic photocatalytic materials.

[0012] Furthermore, in step 2, the heating is continued to be at 1400-1550°C.

[0013] Furthermore, the insulation time of step 3 is 1 to 8 hours.

[0014] Furthermore, the insulation time of step 4 is 3 to 5 hours.

[0015] A kind of NaNbO3 and Na 0.9 K 0.1 NbO3 ferroelectric glass ceramic photocatalytic material, the crystal phase includes NaNbO3 and Na 0.9 K 0.1 NbO3.

[0016] The present invention has the following beneficial effects:

[0017] (1) The present invention adopts a melting method to prepare NaNbO3 and Na 0.9 K 0.1The NbO3 ferroelectric glass ceramic photocatalytic material not only has a simple preparation process and a short production cycle, but also the prepared potassium sodium niobate-based glass ceramic material is a ferroelectric glass ceramic with good transparency and excellent photocatalytic performance. Because the heat preservation during the crystallization process allows the crystal phase to grow while retaining good transparency, and the grain size can be controlled to make the grain size small enough not to scatter light and large enough to have a ferroelectric response, thereby achieving a balance between crystal size and transparency, so that light can pass through the glass matrix to the photocatalytic crystals inside the glass ceramic material, activate the photocatalytic crystals on the inner surface, start the photocatalytic reaction, broaden the light response range of the material, and inhibit the recombination of photogenerated electrons and holes, thereby improving the photocatalytic performance of the glass ceramic material.

[0018] (2) The glass ceramic material prepared by the present invention is a nano-microcrystalline material, NaNbO3 and Na 0.9 K 0.1 NbO3 is a crystalline phase precipitated from the glass matrix during crystallization. NaNbO3 and Na 0.9 K 0.1 As a typical ferroelectric material, NbO3 can exhibit spontaneous polarization. The internal electric field generated by its polarization forces the photogenerated carriers (e- and h+) holes to move in opposite directions, thereby preventing the recombination of electron-hole pairs and improving the carrier separation efficiency, thereby obtaining excellent photocatalytic activity. Moreover, this material has more interfaces and a large specific surface area, which is more conducive to the photocatalytic reaction and can achieve multifunctionality and diversified applications.

[0019] (3) The glass-ceramic material prepared by the present invention can be made into various desired shapes and sizes using models, has a simple recycling process, a low loss rate, and stable physical and chemical properties and good repeatability. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 : UV-visible spectrum of the ferroelectric glass ceramic photocatalytic material prepared in Example 2 of the present invention for photocatalytic degradation of Rhodamine B;

[0021] Figure 2 : The degradation performance spectrum of the ferroelectric glass ceramic photocatalytic material prepared in Example 2 of the present invention for photocatalytic degradation of Rhodamine B;

[0022] Figure 3 : Fitting spectrum of the ferroelectric glass ceramic photocatalytic material prepared in Example 2 of the present invention;

[0023] Figure 4 : A graph showing the first-order rate constants of the photocatalytic degradation of Rhodamine B by the ferroelectric glass-ceramic photocatalytic material prepared in Example 2 of the present invention over time;

[0024] Figure 5 : A graph showing the photocatalytic degradation of Rhodamine B by the ferroelectric glass ceramic photocatalytic materials prepared in Examples 1 to 3 of the present invention;

[0025] Figure 6 : Performance bar graph of photocatalytic degradation of Rhodamine B by ferroelectric glass ceramic photocatalytic materials prepared in Examples 1 to 3 of the present invention;

[0026] Figure 7 : An electron microscope scanning photograph of the ferroelectric glass ceramic photocatalytic material prepared in Example 1 of the present invention;

[0027] Figure 8 : Scanning electron microscope photograph of the ferroelectric glass ceramic photocatalytic material prepared in Example 2 of the present invention;

[0028] Fig. 9 : Scanning electron microscope photograph of the ferroelectric glass ceramic photocatalytic material prepared in Example 3 of the present invention;

[0029] Fig.10 : XRD graphs of the ferroelectric glass-ceramic photocatalytic materials prepared in Examples 1 to 3 of the present invention. DETAILED DESCRIPTION

[0030] The specific contents of the present invention are further explained in detail below in conjunction with the embodiments, but are not intended to limit the present invention.

[0031] Example 1

[0032] Step 1, 30 mol Na2CO3, 5 mol K2CO3, 35 mol Nb2O5 and 20 mol SiO2 are uniformly mixed to obtain a mixture;

[0033] Step 2, add the mixture into a crucible preheated to 1200°C, continue heating to 1450°C to melt the mixture, and keep warm until there are no bubbles, pour the melt into a mold preheated to 200°C to form it;

[0034] Step 3, after the melt of step 2 is formed, it is quickly transferred to an annealing furnace, heated from room temperature to 500°C at a heating rate of 5°C / min and kept at this temperature for 1 hour, and then cooled in the furnace to obtain a glass sample;

[0035] Step 4: Place the glass sample in a muffle furnace, heat it from room temperature to 700°C at a heating rate of 5°C / min and keep it at that temperature for 3 hours. After cooling in the furnace, a glass sample containing NaNbO3 and Na 0.9 K 0.1 NbO3 ferroelectric glass-ceramic photocatalytic materials.

[0036] Example 2

[0037] Step 1, 32.5 mol Na2CO3, 7.5 mol K2CO3, 37.5 mol Nb2O5 and 25 mol SiO2 are uniformly mixed to obtain a mixture;

[0038] Step 2, add the mixture into a crucible preheated to 1150°C, continue heating to 1550°C to melt the mixture, and keep warm until there are no bubbles, pour the melt into a mold preheated to 200°C to form it;

[0039] Step 3, after the melt of step 2 is formed, it is quickly transferred to an annealing furnace, heated from room temperature to 600°C at a heating rate of 5°C / min and kept at this temperature for 2h, and then cooled in the furnace to obtain a glass sample;

[0040] Step 4: Place the glass sample in a muffle furnace, heat it from room temperature to 700°C at a heating rate of 5°C / min and keep it at that temperature for 4 hours. After cooling in the furnace, a glass sample containing NaNbO3 and Na 0.9 K 0.1 NbO3 ferroelectric glass-ceramic photocatalytic materials.

[0041] Example 3

[0042] Step 1, 35 mol Na2CO3, 10 mol K2CO3, 40 mol Nb2O5 and 30 mol SiO2 are uniformly mixed to obtain a mixture;

[0043] Step 2, add the mixture into a crucible preheated to 1250°C, continue heating to 1400°C to melt the mixture, and keep warm until there are no bubbles, pour the melt into a mold preheated to 200°C to form it;

[0044] Step 3, after the melt of step 2 is formed, it is quickly transferred to an annealing furnace, heated from room temperature to 550°C at a heating rate of 5°C / min and kept warm for 3 hours, and then cooled in the furnace to obtain a glass sample;

[0045] Step 4: Place the glass sample in a muffle furnace, heat it from room temperature to 700°C at a heating rate of 5°C / min and keep it at that temperature for 5 hours. After cooling in the furnace, a glass sample containing NaNbO3 and Na 0.9 K 0.1 NbO3 ferroelectric glass-ceramic photocatalytic materials.

[0046] Example 4

[0047] Step 1, 31 mol Na2CO3, 6 mol K2CO3, 36 mol Nb2O5 and 22 mol SiO2 are uniformly mixed to obtain a mixture;

[0048] Step 2, add the mixture into a crucible preheated to 1150°C, continue heating to 1500°C to melt the mixture, and keep warm until there are no bubbles, pour the melt into a mold preheated to 200°C to form it;

[0049] Step 3, after the melt of step 2 is formed, it is quickly transferred to an annealing furnace, heated from room temperature to 550°C at a heating rate of 5°C / min and kept warm for 4 hours, and then cooled in the furnace to obtain a glass sample;

[0050] Step 4: Place the glass sample in a muffle furnace, heat it from room temperature to 700°C at a heating rate of 5°C / min and keep it at that temperature for 5 hours. After cooling in the furnace, a glass sample containing NaNbO3 and Na 0.9 K 0.1 NbO3 ferroelectric glass-ceramic photocatalytic materials.

[0051] Example 5

[0052] Step 1, 33 mol Na2CO3, 8 mol K2CO3, 38 mol Nb2O5 and 27 mol SiO2 are uniformly mixed to obtain a mixture;

[0053] Step 2, add the mixture into a crucible preheated to 1250°C, continue heating to 1450°C to melt the mixture, and keep warm until there are no bubbles, pour the melt into a mold preheated to 200°C to form it;

[0054] Step 3, after the melt of step 2 is formed, it is quickly transferred to an annealing furnace, heated from room temperature to 600°C at a heating rate of 5°C / min and kept at this temperature for 6 hours, and then cooled in the furnace to obtain a glass sample;

[0055] Step 4: Place the glass sample in a muffle furnace, heat it from room temperature to 700°C at a heating rate of 5°C / min and keep it at that temperature for 4 hours. After cooling in the furnace, a glass sample containing NaNbO3 and Na 0.9 K 0.1 NbO3 ferroelectric glass-ceramic photocatalytic materials.

[0056] Example 6

[0057] Step 1, 34 mol Na2CO3, 9 mol K2CO3, 39 mol Nb2O5 and 29 mol SiO2 are uniformly mixed to obtain a mixture;

[0058] Step 2, add the mixture into a crucible preheated to 1200°C, continue heating to 1550°C to melt the mixture, and keep warm until there are no bubbles, pour the melt into a mold preheated to 200°C to form it;

[0059] Step 3, after the melt of step 2 is formed, it is quickly transferred to an annealing furnace, heated from room temperature to 500°C at a heating rate of 5°C / min and kept warm for 8 hours, and then cooled in the furnace to obtain a glass sample;

[0060] Step 4: Place the glass sample in a muffle furnace, heat it from room temperature to 700°C at a heating rate of 5°C / min and keep it at that temperature for 3 hours. After cooling in the furnace, a glass sample containing NaNbO3 and Na 0.9 K 0.1 NbO3 ferroelectric glass-ceramic photocatalytic materials.

[0061] Take the NaNbO3 and Na prepared in Examples 1 to 3 0.9 K 0.1 The ferroelectric glass ceramic photocatalytic material of NbO3 was cut into thin slices of 4×5 mm in size and 0.1-0.2 mm in thickness by a cutting machine. The thin slices were polished and ultrasonically cleaned to obtain the glass ceramic samples to be tested, and their various properties were tested respectively. Table 1 shows the degradation efficiency and photocatalytic rate test results of the glass ceramic samples prepared in Example 2 for degrading Rhodamine B. It can be seen that the degradation efficiency of the glass ceramic catalyst prepared in Example 2 is 46%, and the first-order rate constant of the photocatalytic degradation performance over time is 0.00447, which has excellent photocatalytic performance.

[0062] Table 1: Degradation efficiency and photocatalytic rate of Rhodamine B by glass ceramic samples

[0063] Example 2 Degradation efficiency (%) 46 <![CDATA[Photocatalytic rate (min -1 )]]> 0.00447

[0064] Figure 1 This is the UV-visible absorption spectrum of the glass ceramic sample prepared in Example 2 for photocatalytic degradation of Rhodamine B. It can be seen that: the peak intensity at 553.6nm gradually decreases with the passage of time, and the peak in the photocatalytic process gradually shifts, and the absorption peaks are not in the same position. This result shows that under the action of the KNN glass ceramic photocatalyst, the degradation path of Rhodamine B is different, but the degradation effect is considerable.

[0065] Figure 2 This is the degradation performance spectrum of the glass ceramic sample prepared in Example 2 for photocatalytic degradation of Rhodamine B. It can be seen that within 150 minutes, the efficiency of degradation of Rhodamine B by the three ultra-small 4×5 mm KNN glass ceramics reached 46%. The results show that KNN block glass ceramics have good degradation performance.

[0066] Figure 3 It is the first-order kinetic constant fitting ln(C0 / C)-t diagram of the glass-ceramic sample prepared in Example 2, and the first-order rate constant in the piezoelectric photocatalytic degradation process of the material can be obtained from its slope.

[0067] Figure 4 This is the first-order rate constant spectrum of the photocatalytic degradation performance of the glass-ceramic sample prepared in Example 2 over time. It can be seen that its degradation rate is relatively high, reaching 0.00447 min -1 .

[0068] Figure 5 It is a curve diagram of the photocatalytic degradation of Rhodamine B by the glass ceramic samples prepared in Examples 1 to 3. It can be seen that the ferroelectric glass ceramic photocatalytic material prepared in Example 2 (ie, when the crystallization time of the KNN glass sample is 4 hours) has a good degradation performance, which can reach 46%.

[0069] Figure 6 The performance bar graph of the photocatalytic degradation of Rhodamine B by the glass ceramic samples prepared in Examples 1 to 3 shows that the first-order rate constant of the ferroelectric glass ceramic photocatalytic material prepared in Example 2 (i.e., when the crystallization time of the KNN glass sample is 4 h) is the highest, reaching 0.00447 min -1 .

[0070] Figure 7 to Figure 9 They are respectively electron microscope scanning photographs of glass ceramic samples prepared in Examples 1 to 3 of the present invention, i.e. electron microscope scanning photographs of ferroelectric glass ceramic photocatalytic materials prepared in Examples 1 to 3 (i.e., when the crystallization time of the KNN glass sample is 3h, 4h and 5h, respectively). It can be seen that with the increase of crystallization time, the internal grains of the glass ceramic gradually nucleate and grow and agglomerate, and the catalytic performance of the glass ceramic sample prepared in Example 3 decreases. This is because the internal crystallinity of the glass ceramic sample increases and the grains are seriously agglomerated, resulting in devitrification of the sample, so that light cannot reach the internal grains and cannot trigger a photocatalytic response.

[0071] Fig.10 3 are XRD graphs of the glass-ceramic samples prepared in Examples 1 to 3. It can be seen that as the crystallization time increases, the diffraction peak gradually becomes sharper, proving that the crystallinity is also increasing.

Claims

1. A kind of NaNbO3 and Na 0.9 K 0.1 The method for preparing a NbO3 ferroelectric glass ceramic photocatalytic material is characterized in that: The steps include: Step 1, 30-35 mol Na2CO3, 5-10 mol K2CO3, 35-40 mol Nb2O5 and 20-30 mol SiO2 are uniformly mixed to obtain a mixture; Step 2, add the mixture into a crucible preheated to 1150-1250°C, continue heating to melt the mixture, and keep warm until there are no bubbles, pour the melt into a mold preheated to 200°C to form it; Step 3, after the melt of step 2 is formed, it is quickly transferred to an annealing furnace, heated from room temperature to 500-600°C at a heating rate of 5°C / min and kept warm, and then cooled in the furnace to obtain a glass sample; Step 4: Place the glass sample in a muffle furnace, heat it from room temperature to 700°C at a heating rate of 5°C / min and keep it at this temperature for 3-4 hours. After cooling in the furnace, a glass sample containing NaNbO3 and Na 0.9 K 0.1 NbO3 ferroelectric glass-ceramic photocatalytic materials.

2. The method according to claim 1 containing NaNbO3 and Na 0.9 K 0.1 The method for preparing a NbO3 ferroelectric glass ceramic photocatalytic material is characterized in that: In step 2, the temperature is further heated to 1400-1550°C.

3. The NaNbO3 and Na 0.9 K 0.1 The method for preparing a NbO3 ferroelectric glass ceramic photocatalytic material is characterized in that: The insulation time of step 3 is 1 to 8 hours.

4. The method according to claim 1 containing NaNbO3 and Na 0.9 K 0.1 The method for preparing a NbO3 ferroelectric glass ceramic photocatalytic material is characterized in that: The insulation time of step 4 is 4h.

5. A method as claimed in any one of claims 1 to 4 containing NaNbO3 and Na 0.9 K 0.1 NbO3 ferroelectric glass ceramic photocatalytic material, characterized in that: The crystal phase contains NaNbO3 and Na 0.9 K 0.1 NbO3.

Citation Information

Patent Citations

  • NaNbO3 phase containing Na2O-K2O-Nb2O5-SiO2 low dielectric loss energy storage glass ceramic

    CN108840570A